1997
DOI: 10.1523/jneurosci.17-06-01950.1997
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transcriptional Regulation of the GAP-43 Gene by Specific Sequences in the 3′ Untranslated Region of the mRNA

Abstract: We have shown previously that GAP-43 gene expression during neuronal differentiation is controlled by selective changes in mRNA stability. This process was found to depend on highly conserved sequences in the 3Ј untranslated region (3Ј UTR) of the mRNA. To map the sequences in the GAP-43 3Ј UTR that mediate this post-transcriptional event, we generated specific 3Ј UTR deletion mutants and chimeras with the ␤-globin gene and measured their half-lives in transfected PC12 cells. Our results indicate that there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 53 publications
4
83
0
Order By: Relevance
“…These regions often include a core sequence of ATnG, where n represents a variable repeat of Ϸ3-5 T (uridine) residues. The ATnG core sequence in the upstream elements may enhance efficiency of poly(A) signal usage and mRNA transcript stability of a number of genes (26)(27)(28). In addition, three copies of another motif, ATTTA, a mediator of mRNA destabilization (29), were identified in conserved regions of znf503.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These regions often include a core sequence of ATnG, where n represents a variable repeat of Ϸ3-5 T (uridine) residues. The ATnG core sequence in the upstream elements may enhance efficiency of poly(A) signal usage and mRNA transcript stability of a number of genes (26)(27)(28). In addition, three copies of another motif, ATTTA, a mediator of mRNA destabilization (29), were identified in conserved regions of znf503.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that phylogenetic footprints in 3Ј UTRs are generally enriched in adenosine and uridine (7). Zinc-finger protein 503 (27) References given are recent examples of many. See Discussion for a brief statement of cellular function.…”
Section: Noncoding Regions Of Shark Ppp4r2 and Set Genes In Other Vermentioning
confidence: 99%
“…RNA decay assays were performed as previously described (Tsai et al, 1997). Briefly, cultures were treated with 5 M cadmium, which causes an 8-to 10-fold activation of the human metallothionein-IIA promoter in the pMEP4 vector.…”
Section: Gap-43 Mrna Stability Analysis In Transfected Cell Linesmentioning
confidence: 99%
“…For these studies, a GAP-43 deficient PC12 subclone, PC12-N36, was cotransfected with full length GAP-43 cDNA in the inducible expression vector pMEP4 (Kohn et al, 1996) and with either pDuH or pcDNA3. As in previous studies, cells were exposed for 16 h to 5 M cadmium to induce high levels of GAP-43 mRNA via activation of the metallothionein promoter in pMEP4 (Tsai et al, 1997). After induction, cadmium was removed and the RNA harvested at various time points.…”
Section: Molecular Biology Of the Cell 3194mentioning
confidence: 99%
See 1 more Smart Citation